Comparison of control strategies for the cervical muscles of an average female head-neck finite element model. (25th November 2019) - Putra, I Putu A.; Iraeus, Johan; Thomson, Robert; Svensson, Mats Y.; Linder, Astrid; Sato, Fusako
Abstract: Objective: ViVA OpenHBM is the first open source Human Body Model (HBM) for crash safety assessment. It represents an average size (50th percentile) female and was created to assess whiplash protection systems in a car. To increase the biofidelity of the current model, further enhancements are being made by implementing muscle reflex response capabilities as cervical muscles alter the head and neck kinematics of the occupant during low-speed rear crashes. The objective of this study was to assess how different neck muscle activation control strategies affect head-neck kinematics in low speed rear impacts. Methods: The VIVA OpenHBM head-neck model, previously validated to PMHS data, was used for this study. To represent the 34 cervical muscles, 129 beam elements with Hill-type material models were used. Two different muscle activation control strategies were implemented: a control strategy to mimic neural feedback from the vestibular system and a control strategy to represent displacement feedback from muscle spindles. To identify control gain values for these controller strategies, parameter calibrations were conducted using optimization. The objective of these optimizations was to match the head linear and angular displacements measured in volunteer tests. Results: Muscle activation changed the head kinematics by reducing the peak linear displacements, as compared to the model without muscle activation. For the muscle activation model mimicking the human vestibular system, a good agreement was observed for the horizontal head translation. However, in the vertical direction there was a discrepancy of head kinematic response caused by buckling of the cervical spine. In the model with a control strategy that represents muscle spindle feedback, improvements in translational head kinematics were observed and less cervical spine buckling was observed. Although, the overall kinematic responses were better in the first strategy. Conclusions: Both muscle control strategies improved the head kinematics compared to the passive model and comparable to the volunteer kinematics responses with overall better agreement achieved by the model with active muscles mimicking the human vestibular system.